Macroeconomic Fundamental and Stock Price Index in Southeast Asia Countries A Comparative Study - Wahyudi, Sugeng; Hersugondo, H.; Laksana, Rio Dhani; Rudy, R. (International Journal of Economics and Financial Issues, 2017)
This study analyzed the effect of macroeconomic variables on the composite index in the Southeast Asia Countries. The variable in this study is Inflation, Interest Rate, Exchange Rate, Gross Domestic Products, Crude Oil Price, Primary Commodity Price and Wages in Indonesia, Malaysia, Singapore, Philippine, and Thailand. The study used time series data from the 2001-2015 at each country. By using an analysis technique Threshold Autoregressive Conditional Heteroscedasticity (TARCH), the results from showed that the Inflation Interest Rate, GDP have a negative effect on the composite index in all countries except Thailand; COP has the positive effect in Indonesia, Malaysia, and Singapore, while in the Philippine and Thailand has a positive effect. PCP has a positive effect on the composite index only in Singapore, meanwhile in the Philippine and Thailand has a negative effect on the composite index.Wages have a positive and significant effect on the composite index in all countries. Keywords: Macroeconomic,TARCH, Southeast Asian Countries. JEL Classification: G1